On Investigating the C-transition Curve for Noise Reduction - Putra, A.; Hee, O.K.; Yahaya, S.H. (Journal of Engineering and Technology (JET), 2013)
Among the application of a transition curve is to design the curvature of a highway to ensure smoothness of a moving vehicle in high speed. Investigation on C-Transition Curve (CTC) is presented here on its effect to reduce noise due to airflow. A simple C-Transition Curve is generated from mathematical calculation using a parametric equation and the Computer Fluid Dynamics (CFD) model is developed to assess the turbulence flow generated on the surface of the C-Transition Curve structure. Analysis is also conducted on a semi-circle shape for comparison. It is found that the structure constructed from the C-Transition Curve gives lower Reynolds number. Validation through experiment is also conducted showing lower output of noise level from the C-Transition Curve structure.